Different protein levels in a super-intensive culture of juvenile Pacific white shrimp (Litopenaeus vannamei) in biofloc systems during the early rearing phase - Ítalo Felipe Mascena Braga; Alan Carvalho de Sousa Araújo; Victor Torres Rosas; José Maria Monserrat; Marcelo Borges Tesser; Wilson Wasielesky Junior; Geraldo Foes (Boletim do Instituto de Pesca)
The determination of crude protein level in diets of aquatic organisms allows maximizing growth, decreasing feed costs and improving water quality. A nursery culture of Litopenaeus vannamei was carried out in superintensive biofloc systems using five diets with different protein levels (320 g kg-1 CP, 360 g kg-1 CP, 400 g kg-1 CP, 440 g kg-1 CP and 480 g kg-1 CP); each diet was used in quadruplicates. The experimental period lasted 35 days, and the shrimps (0.59± 0.001 g) were stocked at a density of 600 PL m-³, using 20 experimental units (50 L of useful volume). There were no significant differences in animal survival between treatments (p>0.05). The animals fed with 480 g kg-1 presented higher final weight, SGR when compared to the treatments fed with 320 g kg-1 (p<0.05). Furthermore, feeding shrimp with 32% CP diets results in a reduction in feed utilization and nutrient retention, thus increasing feed costs. Overall, the results show that it is possible to reduce the protein content of L. vannamei diets to up to 360 without affecting the zootechnical performance, survival and antioxidant capacity of the animals.